Emotion regulation and student engagement: Age and gender differences across adolescence - Santos, A. C. (2021)
Research has documented the role of emotions in learning and emotion regulation for student engagement (SE). However, knowledge regarding the predictive power of emotion regulation strategies (ERSs) on SE at different age-groups was lacking. Also, our study aimed to provide data on ERSs use based on age and gender since findings are mixed. This cross-sectional study included a representative sample (N = 1507) of Portuguese students between 10 and 25 years. The sample was divided into four age-groups (10-12, 13-15, 16-18, 19-25). Results indicated ERSs varied with age, with some having a linear developmental pattern (e.g., Putting into Perspective) and others a non-linear (e.g., Positive Reappraisal). SE was higher in females and the youngest and oldest age-groups. Higher SE was related to using more adaptive strategies, and the ERS Refocus on Planning best correlated with the higher SE scores for every age-group.